E-scooter riders and pedestrians: Attitudes and interactions in five countries. Issue 4 (April 2023) - Šucha, Matúš; Drimlová, Elisabeta; Rečka, Karel; Haworth, Narelle; Karlsen, Katrine; Fyhri, Aslak; Wallgren, Pontus; Silverans, Peter; Slootmans, Freya
Abstract: Electric scooters (e-scooters) have become a popular phenomenon internationally; however, their use has raised concerns about pedestrian safety. This study describes the possible effects of the emergence of e-scooters on pedestrians. We focus on the interaction, conflicts, crashes, and attitudes between pedestrians and e-scooter riders and pedestrians' perceived safety in the presence of e-scooters. Data were collected from e-scooter riders and non-riders (n = 3385) through an online survey in Australia, Belgium, the Czech Republic, Norway, and Sweden. Around 20–30% of e-scooter riders rode on sidewalks, whether it is allowed or not. Non-riders of e-scooters tended to report that riding an e-scooter is rather dangerous. Pedestrians, except Australian ones, perceived e-scooter riders (and e-scooter operation) as annoying. Half of the e-scooter riders had experienced a near miss at some point in the past and more than 50% of these near misses included another road user. Up to 10% of the e-scooter riders from all five countries reported having experienced a crash. On the basis of these findings, we believe that the most relevant suggestions for the implications in sustainable (urban) mobility involve separating e-scooter riders and pedestrians.